The effect of common blood sampling types on metabolic screening - Bal, Ceylan; Özyurt, Esra; Yılmaz, Gülsen (Scandinavian journal of clinical and laboratory investigation, 2025)
Capillary blood is often used for dried blood spot samples in metabolic screening tests. This study's objective is to examine the amino acid and acylcarnitine levels in the commonly used sampling types from the same subjects and compare the findings with capillary whole blood samples as the reference. Thirty adult patipicants' blood samples were collected into four different tubes: citrated tubes, serum separating tubes, heparin tubes, and EDTA tubes, respectively and additionally into the syringe. 50 μL blood from each tube and syringe was absorbed onto filter papers. Additionally, capillary whole blood taken from each person's fingertip was absorbed onto the filter paper. All measurements were performed with flow-injection analysis tandem mass spectrometry. In the pairwise comparison of fingertip group and other groups, almost all results were different from the reference group ( < 0.05), except for glutamine and methionine for amino acid analysis. The difference in acylcarnitine levels is not as obvious as in amino acid levels. If other sampling types are used for metabolic screening instead of capillary whole blood, it may lead to low results, especially in amino acid measurements. Additionally, cut-off values should be interpreted, taking into consideration the sampling type, and laboratories should be informed about the sampling type used.